SMART CLASSROOM DESIGN FOR INCLUSIVE MADRASAHS: TRANSFORMING CURRICULUM AND DIGITAL LEARNING ENVIRONMENTS FOR STUDENTS WITH SPECIAL NEEDS - M. Hafiduddin; Abdullah Abdullah (PEDAGOGIK : JURNAL PENDIDIKAN, 2024)
This study aims to analyze smart classroom design in supporting curriculum transformation and the creation of a digital learning environment in inclusive Islamic schools. This study uses a qualitative approach with a case study design to gain an in-depth understanding of the implementation of technology-based learning that is responsive to the diversity of student characteristics. Data were collected through observation, in-depth interviews, and institutional document analysis, then analyzed thematically through a process of reduction, categorization, and meaning-making. The results of the study show two main findings. First, the formation of an adaptive digital curriculum characterized by material differentiation, method flexibility, and a variety of technology-based assessments. Second, the development of an inclusive digital learning ecosystem built through equal access, multimodal support, technology integration, student empowerment, active collaboration, and more meaningful learning experiences. These findings confirm that educational transformation depends not only on the availability of digital devices, but also on integrated and systemic pedagogical design. This study contributes by offering a conceptual model of an inclusive smart classroom that can serve as a reference for educational institutions in developing technology-based learning in a fair, adaptive, and sustainable manner.